Frequency of Arterial Stiffness in Insulin Resistance and Type 2 Diabetes Mellitus Patients in Tertiary Hospital. - Sultana, Fouzia; Sultana, Nilufar; Mollah, Forhadul Hoque; Mamun, Mohammad Al (University Heart Journal, 2025)
Background: Arterial stiffness can predict unfavorable cardiovascular events in patients with various illnesses. It is linked to the presence and progression of diabetes complications such as CVD, retinopathy, neuropathy, and nephropathy. Method: This cross sectional study aims to investigate the frequency of arterial stiffness in patients with Type 2 DM. This study was done in Department of Biochemistry and Molecular Biology, BSMMU from March 2022 to February 2023. Results: 95 type 2 diabetes mellitus patients aged 40 to 70 yrs from Endocrinology and Metabolism OPD of BSMMU were included here. Subjects were divided into two groups on the basis of arterial stiffness which was assessed by measuring brachial ankle pulse wave velocity (bapwv). Group 1 had bapwv ≥1815cm/s was considered as type 2 DM patients with arterial stiffness and Group 2 with bapwv <1815cm/s was considered as type 2 DM patients without arterial stiffness. This study included 49 (51.58%) patients in Group 1 and 46 (48.42%) patients in Group 2 among 95 patients. There was no significant difference in male (29) and female (20) gender in Group 1( p= 0.961). Significant differences between the two groups by age ( 56.96±7.51 in Group 1 and 51.76±8.31 in group 2, p=0.002), systolic blood pressure (128.16±13.79 in G1 and 117.72±10.73 in G2 , p= 0.0001) and diastolic blood pressure (83.98±9.73 in G1 and 79.13±7.84, p=0.009). Also, median values of duration of diabetes, HDL cholesterol (p=0.023) and Fasting insulin (p=0.047) showed significant statistical difference between the two groups. Conclusion: Increased arterial stiffness has been associated with advancing age, higher SBP and DBP, long diabetes Mellitus, high HDL cholesterol. The risk factors of CVD are more common in type 2 patients with increased arterial stiffness. University Heart Journal 2024; 20(2): 61-66